2004
DOI: 10.1002/erv.550
|View full text |Cite
|
Sign up to set email alerts
|

Coping style and vulnerability to eating disorders in adolescent boys

Abstract: The main goal of this study was to analyse the relationship between coping styles and the predisposition to eating disorders in a sample of adolescent boys. The sample comprised 171 males (mean age 15.74 years) and the questionnaires used were the Eating Disorders Inventory-2 (EDI-2) and the Adolescent Coping Scale (ACS). The results indicated that self-blame, a scale of the dimension intropunitive avoidance, characterized by self-blaming excessively in the face of problems, was the strategy most closely linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
1
8
1
1
Order By: Relevance
“…Additionally, relationship, education, and financial stress were associated with boys' dieting. It is unclear why we found these particular associations, although studies suggest that boys who feel overwhelmed by problems may react by engaging in disordered eating behaviors such as dieting (Garcia-Grau et al 2004). Unlike the results seen with girls, boys' bulimic symptoms were indeed directly associated with stress, specifically education and family stress.…”
Section: Discussioncontrasting
confidence: 47%
“…Additionally, relationship, education, and financial stress were associated with boys' dieting. It is unclear why we found these particular associations, although studies suggest that boys who feel overwhelmed by problems may react by engaging in disordered eating behaviors such as dieting (Garcia-Grau et al 2004). Unlike the results seen with girls, boys' bulimic symptoms were indeed directly associated with stress, specifically education and family stress.…”
Section: Discussioncontrasting
confidence: 47%
“…For instance, distraction coping, which aims to divert attention by engaging in secondary behavioral or cognitive activities (Skinner et al, 2003), was associated with both same day and next day binge eating (Freeman & Gil, 2004). Avoidance coping (e.g., escape, disengagement, wishful thinking) (Skinner et al, 2003) has been proposed as a predictor of eating disorders (Aldao, Nolen-Hoeksema, & Schweizer, 2010) and has been reported in patients with anorexia nervosa (AN) or bulimia nervosa (BN) in the U.S. and other countries (Bloks, Spinhoven, Callewaert, Willemse-Koning, & Turksma, 2001; Bloks, Van Furth, Callewaert, & Hoek, 2004; Brytek-Matera & Schiltz, 2013; Fitzsimmons & Bardone-Cone, 2010; Lobera, Estébanez, Fernández, Bautista, & Garrido, 2009; Nagata, Matsuyama, Kiriike, Iketani, & Oshima, 2000; Troop, Holbrey, & Treasure, 1998; Troop, Holbrey, Trowler, & Treasure, 1994), female college students in the U.S. (Dennard & Richards, 2013; Kelly, Lydecker, & Mazzeo, 2012; Wonderlich-Tierney & Vander Wal, 2010; Wolff, Crosby, Roberts, & Wittrock, 2000), and community samples of adolescents in Spain (García-Grau, Fusté, Miró, Saldaña, & Bados, 2002, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…25 In adolescents, emotion-focused coping was found to be associated with disturbed eating attitudes 26 and to be predictive of a predisposition for developing an eating disorder. 27,28 In addition, data from different areas of research, e.g., ecological momentary assessment on adults with BED, bulimia nervosa, 2 and binge eating, 29,30 experimental studies on adults with BED, 31,32 and intervention studies on patients with BED [33][34][35] suggest that binge eating is associated with problematic emotion regulation. Early studies showed that eating psychopathology was associated with an increased use of maladaptive coping and a decreased use of adaptive coping in a nonclinical population 36 and in adults with eating disorders.…”
Section: Introductionmentioning
confidence: 99%